Keratoacanthoma Shares Driver Mutations with Cutaneous Squamous Cell Carcinoma. - Lim, Young H; Fisher, Jonathan M; Bosenberg, Marcus W; Choate, Keith A; Ko, Christine J (J Invest Dermatol, 2016)
Keywords: Aged; Aged, 80 and over; Biomarkers, Tumor; Biopsy; Carcinoma, Squamous Cell; Cohort Studies; Diagnosis, Differential; Exome; Female; Humans; Keratoacanthoma; Loss of Heterozygosity; Male; Middle Aged; Mutation; Polymorphism, Single Nucleotide; Skin; Skin Neoplasms; Whole Exome Sequencing

Somatic Activating RAS Mutations Cause Vascular Tumors Including Pyogenic Granuloma. - Lim, Young H; Douglas, Stephanie R; Ko, Christine J; Antaya, Richard J; McNiff, Jennifer M; Zhou, Jing; Choate, Keith A; Narayan, Deepak (J Invest Dermatol, 2015)
Keywords: Adolescent; Cell Proliferation; Child; Child, Preschool; Female; Gene Expression Regulation, Neoplastic; Granuloma, Pyogenic; Humans; Infant; Infant, Newborn; Male; Mutation; ras Proteins; Vascular Neoplasms

Somatic p.T771R KDR (VEGFR2) Mutation Arising in a Sporadic Angioma During Ramucirumab Therapy. - Lim, Young H; Odell, Ian D; Ko, Christine J; Choate, Keith A (JAMA Dermatol, 2015)
IMPORTANCE: Inhibition of angiogenesis is an effective anticancer strategy because neoplasms require a rich blood supply. Ramucirumab, approved by the US Food and Drug Administration in 2014 to treat gastric adenocarcinomas and non-small cell lung carcinomas, targets vascular endothelial growth factor 2 (VEGFR2). We identified a patient prescribed a regimen of irinotecan hydrochloride, cetuximab, and ramucirumab for metastatic rectal cancer (diagnosed in November 2013 and treated through early January 2015) who developed a new-onset, expanding vascular lesion on his right leg. Via exome sequencing, we found that the lesion contained a single somatic mutation in KDR (encodes VEGFR2), possibly in response to ramucirumab. Vascular tumors are not a known complication of antiangiogenic therapeutics. OBSERVATIONS: Exome sequencing of the well-demarcated, blanching vascular lesion on the lateral right shin revealed a somatic p.T771R mutation in KDR, without evidence of other somatic mutations or loss of heterozygosity. Histological features included lobules of small vessels within the dermis, resembling a tufted angioma. CONCLUSIONS AND RELEVANCE: A potential adverse effect of ramucirumab in combination therapy is the development of sporadic angiomas. The p.T771R mutation was previously implicated in autophosphorylation of VEGFR2 and reported in angiosarcomas alongside other driver mutations. Our observations suggest that this mutation confers a proliferative advantage in the setting of ramucirumab therapy. Patients receiving ramucirumab should be monitored for the development of new vascular lesions.
Keywords: Adult; Angiogenesis Inhibitors; Antibodies, Monoclonal; Antineoplastic Combined Chemotherapy Protocols; Camptothecin; Cetuximab; Hemangioma; Humans; Irinotecan; Male; Mutation; Rectal Neoplasms; Skin Neoplasms; Vascular Endothelial Growth Factor Receptor-2